Putting Social Media and Networking Data in Practice for Education, Planning, Prediction and Recommendation Preface - Kaya, Mehmet; Birinci, Suayip; Kawash, Jalal; Alhajj, Reda (Springer International Publishing Ag, 2020)
[Abstract Not Available]